Elastic Low-Energy Electron Collisions with Methylamine (Journal of Atomic and Molecular Sciences, 2022)
We present ab initio scattering calculations results of low-energy electroncollision with methylamine using $R$-matrix approach within the static-exchange (SE)and static-exchange-polarization (SEP) approximations. The elastic integral, momentumtransfer and differential cross sections are reported. The calculated elastic integralcross sections are in agreement with the available experimental and theoretical data. A $σ^∗$ shape resonances of $^2A'$ symmetry located at 8.9 eV are detected within SEP model.For this dipole molecule Born-closure procedure was used to account for the higherpartial waves $(l > 4)$ to obtain the convergence of the cross section.